13. Zapisz w postaci sumy algebraicznej.
a) (x + 1)(x + 2)(x+3)
b) (x - 2)(x + 5)(2x - 1)
MNOŻENIE SUM ALGEBRAICZNYCH 17
c) (X - 4)(x + 1)
d) (2x - 3)-(x + 2)
u zoning w jak nainrostszei nostri​



Odpowiedź :

Hej!

Zadanie 13 :

(x + 1)(x + 2)(x + 3) =

= (x² + 2x + x + 2)(x + 3) =

= (x² + 3x + 2)(x + 2) =

= x³ + 2x² + 3x² + 6x + 2x + 4 =

= x³ + 5x² + 8x + 4

(x - 2)(x + 5)(2x - 1) =

= (x² + 5x - 2x - 10)(2x - 1) =

= (x² + 3x - 10)(2x - 1) =

= 2x³ - x² + 6x² - 3x - 20x + 10 =

= 2x³ + 5x² - 23x + 10

Zadanie 14 :

(x - 4)(x + 1) =

= x² + x - 4x - 4 =

= x² - 3x - 4

(2x - 3) - (x + 2) =

= 2x - 3 - x - 2 =

= x - 5

Pozdrawiam! - Julka